Characterization of (111)-oriented epitaxial (K0.5Na0.5)NbO3 thick films deposited by hydrothermal method. (12th September 2017) - Shiraishi, Takahisa; Ishikawa, Mutsuo; Uchida, Hiroshi; Kiguchi, Takanori; Kurosawa, Minoru K.; Funakubo, Hiroshi; Konno, Toyohiko J.
Abstract: (111)-oriented epitaxial (K0.5 Na0.5 )NbO3 films of 2 µm thickness were deposited at 240 °C on (111) c SrRuO3 //(111)SrTiO3 substrates by a hydrothermal method. Scanning transmission electron microscopy-energy-dispersive X-ray spectroscopy (STEM-EDS) mapping revealed that a K-rich interfacial region existed in the obtained films. Although the as-deposited films were annealed between 240 and 600 °C in O2 atmosphere, the crystal structure did not markedly change. On the other hand, the leakage current density drastically decreased from 10 −2 –10 0 to 10 −6 A/cm 2 at ±80 kV/cm after annealing above 240 °C. In addition, the relative dielectric constant (εr ), remanent polarization ( P r ), and piezoelectric constant ( d 33, PFM ) increased with increasing annealing temperature from 300 to 600 °C, and their values were respectively 840, 5.7 µC/cm 2, and 64 pm/V for the films annealed at 600 °C.